2015
DOI: 10.1109/tro.2015.2426471
|View full text |Cite
|
Sign up to set email alerts
|

A Class of Explicitly Solvable Vehicle Motion Problems

Abstract: Abstract-A small but interesting result of Brockett is extended to the Euclidean group SE(3) and is illustrated by several examples. The result concerns the explicit solution of an optimal control problem on Lie groups, where the control belongs to a Lie triple system in the Lie algebra. The extension allows for an objective function based on an indefinite quadratic form.Applying the result requires explicit knowledge of the Lie triple systems of the Lie algebra se(3). Hence, a complete classification of the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…which is obtained by taking the derivative of (19) as seen from an observer sited on the (micro-)body frame. Solving equation 25, it can be shown that for the actuation field F a (X) to satisfy equation (25) for every possible value of the strain ξ n it has to be constant along X, or, in other words, the tendon/chamber paths have to be parallel to the midline of the arm and at a constant position with respect to it (Fig. 3-right).…”
Section: Accepted Manuscript N O T C O P Y E D I T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…which is obtained by taking the derivative of (19) as seen from an observer sited on the (micro-)body frame. Solving equation 25, it can be shown that for the actuation field F a (X) to satisfy equation (25) for every possible value of the strain ξ n it has to be constant along X, or, in other words, the tendon/chamber paths have to be parallel to the midline of the arm and at a constant position with respect to it (Fig. 3-right).…”
Section: Accepted Manuscript N O T C O P Y E D I T E Dmentioning
confidence: 99%
“…for every possible ξ a n , which identifies the active DOFs subspace generated by a constant distribution actuation. To plan and follow configuration paths for a chain of sections composing a soft manipulator, it is important to know the geometric properties of the active DOFs subspace Since the completion algebra is the entire Lie algebra of the rigid motion se(3), the system m is called first-order controllable system or Brockett's system in the context of nonholonomic mechanics, of which explicit optimal control solution [24] has been recently extended to the Euclidean group SE(3) in [25]. Those results, made possible by the present screw-based model, could bring about significant improvements in the design and control of soft manipulators.…”
Section: Screw Geometrymentioning
confidence: 99%
“…The Lie triple systems of se(3) were classified in [4,7,12], details of symmetric subspaces of SE(3) can also be found in [14]. It was observed in [4], that most of the symmetric subspaces of SE(3) are linear spaces or the intersection of the Study quadric Q s with a linear subspace.…”
Section: Subgroups and Symmetric Subspacesmentioning
confidence: 99%
“…The theorem can be proved by straightforward inspection of all possible cases. All possibilities were found in [12,4] and [7]. To find points in the symmetric subspaces we need to be able to exponentiate elements of the Lie triple system.…”
Section: Subgroups and Symmetric Subspacesmentioning
confidence: 99%
“…Motivated by this observation, Stramigioli [150] uses this as the defining property of lower pairs. Recently, Selig [145] and Wu et al [158] seized on a concept by Brockett [28] called Lie triple systems. The latter refers to systems of vector fields that are closed under the triple Lie bracket (whereas a Lie algebra is closed under the Lie bracket).…”
Section: Relative Motions As Screw Motionsmentioning
confidence: 99%